Pengembangan Media Pembelajaran Matematika Kelas XI Berbasis Android - Desy Aprima (INTECH, 2021)
This study aims to develop an android-based learning class XI mathematics learning media to support the mathematics learning process both online and face-to-face. This research type was Research and Development (R&D). The steps of the development procedure including: the design stage, the production stage, and the evaluation stage. The subjects in this study were validated in the early stages by experts (design experts, media experts, and subject matter expert). Then proceed with individual-scale product trials, small group-scale trials and field trials. Data collection techniques in this study used a questionnaire. Questionnaires are used to obtain information and data to measure the feasibility of the resulting product. Based on the assessments made by experts, the average percentages were: design experts (79.17), media experts (80.09), subject matter experts (82.09). So, from the overall average value, it can be concluded that on the validation the experts get the eligibility criteria ”Good”. Based on the results of field trials, the percentages obtained are: individual scale (82.33) small scale (82.44), large scale (82.91). So, it can be concluded that the overall average value of the percentage of field trials on the respondents obtained the eligibility criteria of ”Very Good”. In other words, the media developed in this study was considered feasible and very good for use in learning mathematics.